FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PETANI DALAM MENERIMA OPERASI PANGAN RIAU MAKMUR DI SEMBILAN KABUPATEN SE-PROVINSI RIAU - Nuke Fatmasari; Fajar Restuhadi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2015)
The concept of the factors that influence the behavior of farmers in receiving Operasi Pangan Riau Makmur program (OPRM) needs to be done to determine the most significant effect on the program’s accepting. The designing of a model before the implementation of a program, is expected to minimize the unusable things in reality. Modeling analysis SEM (structural equation model) which is used in behavior of farmer’s research designed so as to find a suitable model. Three exogenous variables used in this research, the characteristics of farmers, extension of competence, and competence of the management of farmer groups. Each of these exogenous variables formed by eight indicators, so it is could explain that the skills, systematic program delivery, mastery of the program, and time management, are not included in the indicator models that is affecting the behavior of farmers as endogenous variables, to accept or deny the existence of the program. Farmer behavior is further analyzed the suitability of the model with the independence of farmers. Suitability models were constructed and analyzed is expected to be used by the government or related agencies, before involving the farmers as participants.